Proton Form Factors and Two-Photon Exchange in Elastic Electron-Proton Scattering; Physics of Atomic Nuclei; Vol. 78, iss. 3 - Nikolenko D. M.; Arrington J.; Barkov L. M.; H. de Vries; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Golovin R. A.; Gramolin A. V.; Dmitriev V. F. Vladimir Fedorovich; Zhilich V. N. Viktor Nikolaevich; Zevakov S. A. Sergey Aleksandrovich; Kaminsky V. V. Vyacheslav Viktorovich; Lazarenko B. A. Boris Aleksandrovich; et al. (2015, 2015)
Title screen